Development of a validated UPLCâqTOF-MS/MS method for determination of bioactive constituent from Glycyrrhiza glabra - D.K. Gupta; M.K. Verma; R. Anand; R.K. Khajuria (Elsevier, 2013)
An ultra-performance liquid chromatography quadrupole time of flight mass spectrometry (UPLCâqTOF-MS/MS) method was developed and validated for the simultaneous determination of glycyrrhizin and glycyrrhetic acid. These analytes were separated on a reverse phase C18 column using a mobile phase of acetonitrile:2% acetic acid in water (75:25, v/v) with a flow rate of 200Î¼L/min. The qTOF-MS was operated under multiple reaction monitoring (MRM) mode using the electrospray ionization (ESI) technique with positive ion polarity. A comparison of three different extraction techniques i.e. accelerated solvent extraction (ASE), extraction under ultrasonic waves (USW) and the classical extraction by percolation (CE) method was done and quantification of these extracts was also carried out by the proposed method. Keywords: Glycyrrhiza glabra, Glycyrrhizin, Glycyrrhetic acid, Accelerated solvent extraction, Ultrasonication, Ultra-performance liquid chromatography quadrupole time of flight mass spectrometer (UPLCâqTOF-MS/MS)